Investigating effects of deficit irrigation levels and fertilizer rates on water use efficiency and productivity based on field observations and modeling approaches - Shoukat, M. R.; Shafeeque, Muhammad; Sarwar, A.; Mehmood, K.; Cheema, M. J. M. (MedCrave Group Kft., 2021)
Investigating the effects of optimized fertilizer and irrigation levels on water use efficiency and productivity of wheat crop at small farms is of great importance for precise and sustainable agriculture in Pakistan’s irrigated areas. However, traditional farmer practices for wheat production are inefficient and unsustainable. This study aimed to investigate the effects of deficit irrigation and nitrophos fertilizer levels on bread wheat grain yield, yield parameters, nutrient use and water use efficiencies in bed planting wheat compared to traditional farmers’ practices in the flat sowing method. The two-year field experiment followed a randomized complete block design of three replications, taking three irrigation treatments according to the requirement of crop estimated by CROPWAT model (100% of ETC), deficit irrigation (80% of ETC), and deficit irrigation 60% of ETC and three nitrophos fertilizer treatments (farmer practice 120 kg N ha-1, optimized 96 kg N ha-1, and 84 kg N ha-1) at different growth stages. Crop ETC was calculated using the FAO CROPWAT 8.0 model from the last ten years (2003-2013) average climate data of the experimental station. The traditional farmer practice treatment was included as a control treatment with a flat sowing method compared with other sown-by-bed planter treatments. All treatments were provided with an equivalent amount of fertilizer at the basal dose. Before the first and second irrigation, top-dressing fertilizer was used in traditional farmers’ treatment at the third leaf and tillering stages. It was applied in optimized treatments before the first, second, and third irrigation at the third leaf, tillering and shooting stages, respectively, under the bed planting method. The deficit level of irrigation (80% of ETc) and optimized fertilizer (96 kg N ha-1) showed the optimum grain yield, nutrient use, and water use efficiencies, with 20% reduced irrigation water and fertilizer levels than traditional farming practice. The results suggest that bread wheat should be irrigated with 80% of ETC and applied 96 kg N ha-1 nitrophos fertilizer at the third leaf, tillering, and shooting stages to achieve higher grain yield and water and nutrient use efficiencies under bed planting.